High-conductivity bridged silicon-carbon composite material as well as preparation method and application thereof
By growing carbon nanotubes on the porous carbon surface and attaching a nanosilicon layer, and then covering the carbon cladding layer to form a highly conductive bridged silicon-carbon composite material, the problems of large expansion and poor circulation performance of lithium-ion battery materials are solved, and the effects of high capacity, low expansion and long circulation performance are achieved.
Patent Information
- Application Number
- CN202510001657.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
AI Technical Summary
While the silicon-carbon materials of existing lithium-ion batteries meet high capacity, they have problems such as large expansion and poor circulation performance, and traditional preparation methods have safety hazards or poor material performance.
Using a highly conductive bridged silicon-carbon composite material, a core-shell structure is formed by growing carbon nanotubes in situ on the porous carbon surface, and a nanosilicon layer is attached to its pores and surfaces, and then a carbon cladding layer is coated to form a core-shell structure. The preparation method of the material includes porous carbonic acid treatment, mixing with soluble metal salts, calcined growth carbon nanotubes, silicon vapor deposition and carbon coating formation.
A high-conductive bridged silicon-carbon composite material with high capacity, low expansion and long cycle performance has been achieved, which significantly improves the mechanical strength and conductivity of the material, and improves the first lithium embedded capacity, first deliques and cycle performance of lithium-ion batteries.
Smart Images

Figure CN119650665A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a highly conductive bridged silicon-carbon composite material and a preparation method and application thereof. Background Art
[0002] As the power market's demand for high-energy-density lithium-ion batteries increases, silicon-carbon materials must meet high capacity requirements while still taking into account low expansion and long cycle performance.
[0003] The traditional sand grinding method grinds micron silicon to nanometer level, which takes a long time. During the process, nano silicon particles are easy to agglomerate. The resulting silicon-carbon material still has defects such as large expansion and poor cycle performance. The vapor deposition method uses porous carbon as the substrate and fills silicon particles (small silicon grains, about 3nm) in its pores, which can effectively reduce the expansion of silicon-carbon materials and improve their cycle performance. Patent CN114976026A uses the Schiff base condensation method to prepare a porous carbon substrate, which is then placed in a reactor for silane deposition, and finally coated with soft carbon on its surface by CVD, thereby obtaining a silicon-based negative electrode material with high capacity and high initial efficiency. However, silicon-containing gas is flammable and explosive, and has high requirements for the air tightness of the equipment, which poses a safety hazard in actual production. Patent CN 110048092B uses plasma to evaporate coarse silicon powder into silicon vapor, which is then attached to the graphite surface in contact with graphite in a condensation chamber, then coated by CVD, and finally mixed with a binder and calcined to obtain a silicon-carbon composite material, which can improve the initial efficiency and cycle performance of the material. However, silicon vapor quickly condenses when it contacts the graphite surface, which easily causes the accumulation and agglomeration of nano-silicon particles. In addition, nano-silicon is attached to the graphite surface and is not in close contact with the graphite, so it cannot bind the nano-silicon well, affecting the material rate and long cycle performance. Patent CN117174841A uses high-frequency plasma equipment to gasify micron-sized silicon powder and then grows it in situ in the pores of porous hard carbon materials. With porous hard carbon as the substrate, more nano-silicon particles can be deposited in the pores that penetrate, so that the resulting silicon-carbon material has a higher specific capacity, while alleviating the damage to the structure caused by its volume expansion, and improving the material's cycle performance and charging performance. However, when silicon vapor contacts porous hard carbon materials, it cannot be guaranteed to be completely deposited in the pores. Without further carbon coating treatment, it is easy to cause a large specific surface area, affecting the initial effect. At the same time, the exposed silicon particles on the surface are easy to break, affecting the cycle performance. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a highly conductive bridged silicon-carbon composite material with high capacity, low expansion and long cycle performance; another purpose of the present invention is to provide a method for preparing a highly conductive bridged silicon-carbon composite material with high capacity, low expansion and long cycle performance.
[0005] The invention discloses a highly conductive bridged silicon-carbon composite material, comprising a core-shell structure with an inner core and an outer shell, wherein the inner core is porous carbon and carbon nanotubes grown in situ on the surface of the porous carbon, and a nano-silicon layer is attached to the pores and surfaces of the porous carbon and the carbon nanotubes; and the outer shell is a carbon coating layer.
[0006] The present invention also discloses a method for preparing a highly conductive bridged silicon-carbon composite material, comprising the following steps:
[0007] (1) treating the porous carbonic acid and then washing it with a solvent until it becomes neutral; mixing the porous carbon and the soluble metal salt in a solvent, and then removing the solvent from the mixture to obtain a dry powder A;
[0008] (2) placing dry powder A at a temperature of 400-600°C, introducing a mixture of hydrogen and argon for the first stage of calcination to reduce the metal ions in dry powder A to metal elements, then controlling the temperature at 500-950°C, introducing a mixture of a gaseous carbon source, hydrogen and argon for the second stage of calcination to in-situ grow carbon nanotubes on the porous carbon surface, and cooling; taking out the obtained powder and placing it in olefinic acid to react and remove the metal, washing with a solvent until neutral, and removing the solvent to obtain dry powder B;
[0009] (3) Silicon powder is placed in a high-frequency plasma reaction chamber to form silicon vapor, which is carried into a transition chamber by a protective gas. Dry powder B is sent into the transition chamber to adsorb the silicon vapor and condense to obtain dry powder C;
[0010] (4) The dry powder C is heated to 400-800° C. in a protective gas atmosphere, and a gaseous carbon source is introduced to deposit a carbon coating layer on the surface of the dry powder C. After cooling, a highly conductive bridged silicon-carbon composite material as described above is obtained.
[0011] The porous carbon is treated with an acid to help form oxygen-containing functional groups on the surface of the porous carbon, thereby forming sites for fixing metal ions. The solvent may be water or other solvents that can dissolve metal salts.
[0012] Furthermore, in step (1), the porous carbon comprises one of biomass porous carbon, resin-based porous carbon, petroleum coke porous carbon, and coal-based porous carbon; the D50 of the porous carbon is 5-10 μm, and the specific surface area is 1500-2200 m 2 / g, pore volume is 0.7-1.0cm 3 / g; the operation of porous carbonic acid treatment is: adding the porous carbon to a mixed acid of 98wt% H2SO4 and HNO3 and stirring for 30-120min; wherein the mass ratio of H2SO4 and HNO3 is 1-4:1.
[0013] Porous carbon substrate is the core material for vapor-deposited silicon carbon. The specific surface area, pore size distribution and size of porous carbon materials directly affect the uniformity and deposition depth of nano-silicon deposition. Limiting the specific surface area, pore size distribution and size of porous carbon materials within the above range is beneficial to improving the uniformity of nano-silicon deposition.
[0014] Furthermore, the soluble metal salt is one of ferric chloride, ferrous chloride, ferric nitrate, ferrous nitrate, ferric acetate, ferrous acetate, nickel chloride, nickel nitrate, nickel sulfate, nickel acetate, cupric chloride, cupric nitrate, and cupric acetate; the mass ratio of the porous carbon to the soluble metal salt is 5-15:1; and the solvent is water.
[0015] Gas-phase carbon sources include, but are not limited to, methane, ethylene, and acetylene.
[0016] Furthermore, in step (2), the flow rate of the mixed gas of argon and hydrogen in the first stage of calcination is 0.1-0.8 L / min; the flow rate of hydrogen accounts for 5-30%; and the insulation time is 1-5 h; the flow rate of the mixed gas of gaseous carbon source, hydrogen and argon in the second stage of calcination is 0.1-1 L / min; the flow rate of the gaseous carbon source accounts for 10-40%, and the flow rate of hydrogen accounts for 1-10%; and the insulation time is 1-5 h.
[0017] Hydrogen reduces the metal ions fixed on the porous carbon surface into metal atoms, and the metal atoms in situ catalyze the growth of carbon nanotubes in the presence of a gaseous carbon source.
[0018] Furthermore, in step (3), the silicon powder D50 is 10-100 μm; and the mass ratio of silicon powder to dry powder B is 0.8-1.5:1.
[0019] Using coarse silicon powder as raw material, plasma technology is used to form silicon vapor for vapor deposition, which is cheap and highly safe.
[0020] Furthermore, the discharge current in the plasma reaction chamber is 80-250A, and the working voltage is 100-200V; the temperature in the transition chamber is 400-750°C.
[0021] Temperatures higher than 750°C will cause SiC to form impurities; temperatures lower than 400°C will cause a large number of silicon particles to accumulate on the surface of the carbon material, resulting in uneven distribution of silicon particles.
[0022] Furthermore, in the step (4), the carbon source gas is introduced into a high-frequency plasma device for treatment and then reacts with the dry powder C for vapor deposition.
[0023] When the carbon coating layer is formed, it is carried out in a rotary kiln, and the rotation speed of the rotary kiln cavity is 0.1-2r / min; the flow rate of the treated acetylene gas entering the rotary kiln is controlled at 0.1-1L / min.
[0024] High-frequency plasma can provide a large amount of energy to promote the cracking of gas-phase carbon sources, thereby improving reaction efficiency. The gas-phase carbon source is treated with high-frequency plasma to fully crack it, thereby solving the problem that the gas-phase deposited carbon coating layer in the prior art mostly uses low-temperature carbon coating, has low carbon source utilization, and has poor carbon layer uniformity.
[0025] Furthermore, the discharge power processed by the high-frequency plasma equipment is 100-1000W.
[0026] The present invention also discloses an application of a highly conductive bridged silicon-carbon composite material. The highly conductive bridged silicon-carbon composite material obtained by the preparation method described above is applied to the preparation of lithium-ion batteries. The lithium-ion batteries prepared thereby have a first lithium insertion capacity greater than 2300mAh / g; and a first lithium removal capacity greater than 2100mAh / g.
[0027] The present invention provides a highly conductive bridged silicon-carbon composite material, in which carbon nanotubes are grown in situ on the surface of porous carbon. The contact between particles is similar to "bridge", forming a "point-line" conductive network, which improves the intrinsic conductivity of the composite material and accelerates the electron transfer rate. At the same time, carbon nanotubes have extremely high strength and hardness. When introduced into porous carbon materials, the mechanical strength of the porous carbon substrate can be significantly improved, and the expansion of nano-silicon during charging and discharging can be better restrained, so that it exhibits high capacity, high initial efficiency, long cycle and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is an XRD diagram of the highly conductive bridged silicon-carbon composite material prepared in Example 1 of the present invention;
[0029] Figure 2 1 is a graph showing the test results of the powder electrical conductivity of the silicon-carbon composite material of Example 1 and Comparative Example 1 of the present invention;
[0030] Figure 3 is the charge and discharge curve of the highly conductive bridged silicon-carbon composite material of Example 1 of the present invention;
[0031] Figure 4 It is a graph showing the cycle performance test results of the silicon-carbon composite material of Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.
[0034] Example 1
[0035] Preparation of highly conductive bridged silicon-carbon composite materials:
[0036] (1) Take 10g of resin-based porous carbon (D50 is 7μm, specific gravity is 2000m 2 / g, pore volume 0.9m 3 / g) was added into 100mL of a mixed acid of 98% H2SO4 and HNO3 (mass ratio 2:1) and stirred for 60min. The porous carbon was washed with water until neutral and then dispersed in ultrapure water (mass of porous carbon: mass of ultrapure water = 10:90). 1g of nickel nitrate hexahydrate was added and stirred at 80°C for 2h. The powder was rotary evaporated at 90°C and dried in a vacuum oven to obtain dry powder A.
[0037] (2) Dry powder A was placed in a tubular furnace, and a mixture of argon and hydrogen (hydrogen accounted for 20%, and the total flow rate was 0.2 L / min) was introduced. The calcination temperature was 600 °C and kept warm for 1 h; the temperature was raised to 900 °C, and a mixture of methane, argon and hydrogen (methane accounted for 20%, argon accounted for 75%, and the total flow rate was 0.2 L / min) was introduced. The temperature was kept warm for 2 h to obtain dry powder B.
[0038] (3) Coarse silicon powder with a D50 of 50 μm was placed in a high-frequency plasma reaction chamber, and argon was used as the protective gas. The working current of the high-frequency plasma generator was set to 120A and the working voltage was set to 130V, so that the micron silicon in the reaction chamber formed silicon vapor. Dry powder B (the mass ratio of coarse silicon powder to dry powder B was 1.1:1) was placed in a transition chamber. The temperature of the transition chamber was 580°C. Silicon vapor entered the transition chamber driven by 1L / min argon and was then sent to the condensation chamber to obtain dry powder C.
[0039] (4) Dry powder C is placed in a rotary kiln with a furnace speed of 0.8 r / min. Nitrogen is introduced and the temperature is raised to 500°C at a rate of 5°C / min. Acetylene gas is introduced into a high-frequency plasma device (power of 500 W) for treatment and then introduced into the rotary kiln at a rate of 0.5 L / min. The mixture is kept warm for 2 h and then cooled to obtain a highly conductive bridged silicon-carbon composite material.
[0040] The highly conductive bridged silicon-carbon composite material prepared in Example 1 was subjected to XED test. The test results are as follows: Figure 1 As shown, it can be seen from the figure that the prepared highly conductive bridged silicon-carbon composite material has an amorphous structure.
[0041] Example 2
[0042] Preparation of highly conductive bridged silicon-carbon composite materials:
[0043] (1) Take 10g coconut shell-based porous carbon (D50 is 7μm, specific gravity is 1850m2 / g, pore volume 0.85m 3 / g) was added into 100mL of a mixed acid of 98% H2SO4 and HNO3 (mass ratio 3:1) and stirred for 90min. The porous carbon was washed with water until neutral and then dispersed in ultrapure water (mass of porous carbon: mass of ultrapure water = 10:90). 1g of ferric chloride was added and stirred at 80°C for 2h. The powder was rotary evaporated at 90°C and dried in a vacuum oven to obtain dry powder A.
[0044] (2) Dry powder A was placed in a tubular furnace, and a mixture of argon and hydrogen (hydrogen accounted for 25%, and the total flow rate was 0.25 L / min) was introduced. The calcination temperature was 600°C and kept warm for 1 hour; the temperature was raised to 750°C, and a mixture of acetylene, argon and hydrogen (acetylene accounted for 20%, argon accounted for 75%, and the total flow rate was 0.25 L / min) was introduced. The mixture was kept warm for 2 hours to obtain dry powder B.
[0045] (3) Coarse silicon powder with a D50 of 40 μm was placed in a high-frequency plasma reaction chamber, and argon was used as the protective gas. The working current of the plasma generator was set to 100 A and the working voltage was set to 110 V, so that the micron silicon in the reaction chamber formed silicon vapor. Dry powder B (the mass ratio of coarse silicon powder to dry powder B was 1.2:1) was placed in a transition chamber. The temperature of the transition chamber was 600 °C. The silicon vapor entered the transition chamber driven by 0.8 L / min argon and was then sent to the condensation chamber to obtain dry powder C.
[0046] (4) Dry powder C is placed in a rotary kiln with a furnace speed of 0.5 r / min. Nitrogen is introduced and the temperature is raised to 520°C at 5°C / min. Acetylene gas is introduced into a high-frequency plasma device (power of 400 W) for treatment and then introduced into the rotary kiln at 0.8 L / min. The mixture is kept warm for 2 h and then cooled to obtain a highly conductive bridged silicon-carbon composite material.
[0047] Example 3
[0048] Preparation of highly conductive bridged silicon-carbon composite materials:
[0049] (1) Take 10g of resin porous carbon (D50 is 8μm, specific gravity is 1900m 2 / g, pore volume 0.9m 3 / g) was added into 100mL of a mixed acid of 98% H2SO4 and HNO3 (mass ratio 2:1) and stirred for 60min. The porous carbon was washed with water until neutral and then dispersed in ultrapure water (mass of porous carbon: mass of ultrapure water = 10:90). 1g of copper nitrate hexahydrate was added and stirred at 90°C for 4h. The powder was rotary evaporated at 90°C and dried in a vacuum oven to obtain dry powder A.
[0050] (2) Dry powder A was placed in a tubular furnace, and a mixture of argon and hydrogen (hydrogen accounted for 10%, total flow rate was 0.2 L / min) was introduced. The calcination temperature was 580°C and kept warm for 3 h; the temperature was raised to 950°C, and a mixture of methane, argon and hydrogen (methane accounted for 25%, argon accounted for 70%, total flow rate was 0.2 L / min) was introduced. The mixture was kept warm for 1.5 h to obtain dry powder B.
[0051] (3) 50 is 50 μm coarse silicon powder placed in a high-frequency plasma reaction chamber, argon is used as the protective gas, the plasma generator is set to work at a current of 110A and a voltage of 150V, so that the micron silicon in the reaction chamber forms silicon vapor, and dry powder B (wherein the mass ratio of coarse silicon powder to dry powder B is 1.1:1) is placed in a transition chamber. The temperature of the transition chamber is 600°C, and silicon vapor enters the transition chamber driven by 1.2L / min argon gas, and is then sent to the condensation chamber to obtain dry powder C.
[0052] (4) Dry powder C is placed in a rotary kiln with a furnace speed of 0.5 r / min. Nitrogen is introduced and the temperature is raised to 500°C at a rate of 5°C / min. Acetylene gas is passed into a high-frequency plasma device (power of 400 W) for treatment and then passed into the rotary kiln at a rate of 0.5 L / min. The mixture is kept warm for 2 h and then cooled to obtain a highly conductive bridged silicon-carbon composite material.
[0053] Comparative Example 1
[0054] Preparation of silicon-carbon composite materials:
[0055] (1) Coarse silicon powder with a D50 of 50 μm is placed in the reaction chamber, argon is used as the protective gas, and the plasma generator is set to work at a current of 120A and a voltage of 130V to make the micron silicon in the reaction chamber form silicon vapor. 2 / g, pore volume 0.9m 3 / g, where the mass ratio of coarse silicon powder and resin porous carbon is 1.1:1) is placed in a transition chamber with a temperature of 580°C. Silicon vapor enters the transition chamber driven by 1L / min argon gas and is then sent to a condensation chamber to obtain dry powder.
[0056] (2) The dry powder is placed in a rotary kiln with a furnace speed of 0.8 r / min. Nitrogen is introduced and the temperature is raised to 500°C at 5°C / min. Acetylene gas is introduced into a plasma device (power of 500 W) for treatment and then introduced into the rotary kiln at 0.5 L / min. The temperature is kept for 2 h and the silicon-carbon composite material is obtained after the temperature is lowered.
[0057] Performance Test:
[0058] The silicon-carbon composite materials obtained in Example 1 and Comparative Example 1 were subjected to a powder conductivity test. The test results are as follows: Figure 2 shown.
[0059] Depend on Figure 2 It can be seen that compared with Comparative Example 1, the composite silicon-carbon material obtained in Example 1 has carbon nanotubes grown on the surface of porous carbon, and the contact between particles is similar to "bridging", forming a "point-line" conductive network, which greatly improves the intrinsic conductivity of the silicon-carbon composite material.
[0060] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Example 1 were assembled into a 2032 button battery for evaluation. The specific scheme was to mix the silicon-carbon composite material, conductive agent SP (conductive carbon black), conductive agent VGCF (carbon nanofiber), and binder LA136 (polyacrylic acid) in a ratio of 75:5:10:10, and use water as a solvent to coat the slurry on copper foil. The counter electrode was a lithium sheet, and the diaphragm was a Celgard 2400 microporous polypropylene film. The charge and discharge cut-off voltage was 0.005-1.5V, and the discharge rate was first 0.1C to 0.005V, and then 0.02C to 0.005V to fully discharge it. The charge rate was 0.1C to charge to 1.5V. The test results are as follows Figure 3 And as shown in Table 1.
[0061] Table 1 shows the power-on test results of Examples 1-3 and Comparative Example 1:
[0062] Material First lithium insertion capacity (mAh / g) First lithium removal capacity (mAh / g) First efficiency (%) Example 1 2355.9 2130.34 90.43 Example 2 2432.9 2183.9 89.8 Example 3 2383.9 2133.8 89.51 Comparative Example 1 2245.6 1958.2 87.2
[0063] Compared with Comparative Example 1, Examples 1-3 have better first lithium insertion capacity, first lithium removal capacity and first efficiency.
[0064] like Figure 3 As shown, Example 1 exhibits a high first delithiation capacity, a 1.5V delithiation capacity of 2130.34 mAh / g, and a first efficiency of 90.43%.
[0065] like Figure 4 As shown, compared with Comparative Example 1, the capacity retention rate of Example 1 after 90 cycles is much greater than that of Comparative Example 1. This is because the introduction of carbon nanotubes increases the mechanical strength of the material, improves the mechanical strength and intrinsic conductivity of the porous carbon substrate, and exhibits better long cycle performance.
[0066] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A highly conductive bridged silicon-carbon composite material, characterized in that: It comprises a core-shell structure with a core and an outer shell, wherein the core is porous carbon and carbon nanotubes grown in situ on the porous carbon surface, and nano silicon layers are attached to the pores and surfaces of the porous carbon and the carbon nanotubes; and the outer shell is a carbon coating layer.
2. A method for preparing a highly conductive bridged silicon-carbon composite material, characterized in that: The following steps are involved: (1) treating the porous carbonic acid and then washing it with a solvent until it becomes neutral; mixing the porous carbon and the soluble metal salt in a solvent, and then removing the solvent from the mixture to obtain a dry powder A; (2) placing dry powder A at a temperature of 400-600°C, introducing a mixture of hydrogen and argon for the first stage of calcination to reduce the metal ions in dry powder A to metal elements, then controlling the temperature at 500-950°C, introducing a mixture of a gaseous carbon source, hydrogen and argon for the second stage of calcination to in-situ grow carbon nanotubes on the porous carbon surface, and cooling; taking out the obtained powder and placing it in olefinic acid to react and remove the metal, washing with a solvent until neutral, and removing the solvent to obtain dry powder B; (3) Silicon powder is placed in a high-frequency plasma reaction chamber to form silicon vapor, which is carried into a transition chamber by a protective gas. Dry powder B is sent into the transition chamber to adsorb the silicon vapor and obtain dry powder C through condensation; (4) The dry powder C is heated to 400-800° C. in a protective gas atmosphere, a gaseous carbon source is introduced, and a carbon coating layer is deposited on the surface of the dry powder C. After cooling, a highly conductive bridged silicon-carbon composite material as described in claim 1 is obtained.
3. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 2, characterized in that: In step (1), the porous carbon includes one of biomass porous carbon, resin-based porous carbon, petroleum coke porous carbon, and coal-based porous carbon; the D50 of the porous carbon is 5-10 μm, and the specific surface area is 1500-2200 m 2 / g, pore volume is 0.7-1.0cm 3 / g; the operation of porous carbonic acid treatment is: adding the porous carbon to a mixed acid of 98wt% H2SO4 and HNO3 and stirring for 30-120min; wherein the mass ratio of H2SO4 and HNO3 is 1-4:
1.
4. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 3, characterized in that: The soluble metal salt is one of ferric chloride, ferrous chloride, ferric nitrate, ferrous nitrate, ferric acetate, ferrous acetate, nickel chloride, nickel nitrate, nickel sulfate, nickel acetate, cupric chloride, cupric nitrate and cupric acetate; the mass ratio of the porous carbon to the soluble metal salt is 5-15:1; and the solvent is water.
5. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 2, characterized in that: In the step (2), the flow rate of the mixed gas of argon and hydrogen in the first stage of calcination is 0.1-0.8 L / min; the flow rate of hydrogen accounts for 5-30%; and the insulation time is 1-5 h; the flow rate of the mixed gas of gaseous carbon source, hydrogen and argon in the second stage of calcination is 0.1-1 L / min; the flow rate of the gaseous carbon source accounts for 10-40%, and the flow rate of hydrogen accounts for 1-10%; and the insulation time is 1-5 h.
6. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 2, characterized in that: In the step (3), the silicon powder D50 is 10-100 μm; and the mass ratio of silicon powder to dry powder B is 0.8-1.5:
1.
7. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 6, characterized in that: The discharge current in the plasma reaction chamber is 80-250A, and the working voltage is 100-200V; the temperature in the transition chamber is 400-750°C.
8. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 2, characterized in that: In the step (4), the carbon source gas is introduced into a high-frequency plasma device for treatment and then reacts with the dry powder C for vapor deposition.
9. The method for preparing a highly conductive bridged silicon-carbon composite material according to claim 8, characterized in that: The discharge power processed by the high-frequency plasma equipment is 100-1000W.
10. An application of a highly conductive bridged silicon-carbon composite material, characterized in that: The highly conductive bridged silicon-carbon composite material obtained by the preparation method according to any one of claims 2 to 9 is used in the preparation of lithium-ion batteries, and the lithium-ion battery obtained by the preparation has a first lithium insertion capacity greater than 2300 mAh / g; The first lithium desorption capacity is greater than 2100mAh / g.
Citation Information
Patent Citations
A silicon-carbon composite material for lithium batteries and its preparation method
CN110048092B
Silicon-based negative electrode material and preparation method and application thereof
CN114976026A
Composite lithium storage material for lithium ion battery as well as preparation method and application of composite lithium storage material
CN117174841A
Cited By
Power type porous carbon composite material and preparation method thereof, silicon-carbon negative electrode material and lithium ion battery
CN121536926A
A power type porous carbon composite material, a preparation method thereof, a silicon-carbon negative electrode material and a lithium ion battery
CN121536926B
Silicon-carbon negative electrode material, silicon-carbon composite material, silicon-carbon negative electrode slurry and preparation method
CN121726390A